PEMANFAATAN INTERNET OF THINGS OLEH PEREMPUAN DI KOTA MANADO - Runtukahu, Gladys; Niode, Burhan; Sampe, Stefanus; Rares, Joyce Jacinta; Waleleng, Grace Jane (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
The Internet of Things (Internet of Things ), also known as the connectivity of various physical objects to the internet for autonomous data exchange, has become an integral part of human life. Its impact extends beyond the conventional use of smartphones for social media, influencing diverse aspect of daily activities. This research focuses on exploring the extent to which women in the city of Manado engage with Internet of Things . Employing a descriptive qualitative approach, with theory of utilization and using phenomenological methods, the study utilizes a Combination Purposive sampling technique based on the analysis of individuals actively involved in various activity (Patton, 2002). Both secondary and primary data sources are employed with the researcher serving as the primary instrument. Initially, ten informants were selected, but to enhance information gathering, an online platform survey was distributed, resulting in responses from twenty one informants. The study reveals that women in Manado extensively leverage Internet of Things technology, particularly through Internet of Things – based application on smartphones, while also utilizing devices in their artificial environments due to their availability.